Red Blood Cell Metabolism in Pyruvate Kinase Deficient Patients - Roy, Micaela K.; Cendali, Francesca; Ooyama, Gabrielle; Gamboni, Fabia; Morton, Holmes; D’Alessandro, Angelo (Frontiers in Physiology, 2021)
Background: Pyruvate kinase deficiency (PKD) is the most frequent congenital enzymatic defect of glycolysis, and one of the most common causes of hereditary non spherocytic hemolytic anemia. Therapeutic interventions are limited, in part because of the incomplete understanding of the molecular mechanisms that compensate for the metabolic defect. Methods: Mass spectrometry-based metabolomics analyses were performed on RBCs from healthy controls (n=10) and PKD patients (n=5). Results: In PKD patients, decreases in late glycolysis were accompanied by accumulation of pentose phosphate pathway metabolites, as a function of oxidant stress to purines (increased breakdown and deamination). Markers of oxidant stress included increased levels of sulfur-containing compounds (methionine and taurine), polyamines (spermidine and spermine). Markers of hypoxia such as succinate, sphingosine 1-phosphate and hypoxanthine were all elevated in PKD subjects. Membrane lipid oxidation and remodeling was observed in RBCs from PKD patients, as determined by increases in the levels of free (poly-/highly-unsaturated) fatty acids and acyl-carnitines. Conclusion: In conclusion, in the present study we provide the first overview of RBC metabolism in patients with PKD. Though limited in scope, the study addresses the need for basic science to investigate pathologies targeting underrepresented minorities (Amish population in this study), with the ultimate goal to target treatments to health disparities